FONDASI PENELITIAN ILMIAH: KETERKAITAN KONSEPTUAL ANTARA MASALAH, TUJUAN, HIPOTESIS, DAN METODE ANALISIS DATA - Nur Haswinda; Adinda Regina; Afdhal Kurnia Pratama; Ahmad Zikri Alamsha; Alfiyyah Nabila; Imawati Tanjung; Kiranti Pratiwi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Scientific research is a systematic process designed to answer research questions through structured methodological steps. The foundation of scientific research consists of four main elements: research problem, research objectives, hypothesis, and data analysis methods. This study aims to examine the conceptual relationships among these four elements and their impact on research quality. The method used is a literature review with a descriptive-analytical approach. Data were collected from various academic sources such as journals, books, and scientific publications related to scientific research. The results indicate that the conceptual relationship between the research problem, research objectives, hypothesis, and data analysis methods is a crucial basis for building a logical and focused research framework. A clear research problem guides the formulation of specific research objectives, which then form the foundation for developing testable hypotheses. The choice of data analysis methods is based on the type of data and proposed hypotheses, ensuring alignment between the analysis methods and the research focus. By understanding these interconnections, researchers can improve the quality of their studies and strengthen the validity and reliability of their results. This study is expected to serve as a reference for researchers in designing a more solid and structured foundation for scientific research.